JAIME SOMMERS. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information on the character of Jaime Sommers in the science-fiction adventure television series "The Bionic Woman," is presented. Sommers gets her legs, arm, and ear replaced with bionic body parts after suffering from a sky-diving accident. Actress Lindsay Wagner plays the character of Sommers.